Uji Penghambatan Xantin Oksidase secara In Vitro Ekstrak Kulit Rambutan - Putri, Nurul Eka; Rissyelly, Rissyelly; Mauldina, Marista Gilang (Pharmaceutical Sciences and Research, 2016)
Hyperuricemia is a condition have higher uric acid levels that can cause a cumulation uric acid crystals in the tissues. Xanthine oxidase is an enzyme which catalyze the oxidation of hypoxanthine into xanthine and into uric acid.Therefore, the inhibition of xanthine oxidase will reduce ammount of uric acid. This research aims to determine xanthine oxidase inhibition activity and also to identify chemical constituent group of extract rambutan (Nephelium lappaceum Linn.) skin. Rambutan fruit skin was extracted by graded maceration using a three solvent, based on polarity the solvent are n-hexane, ethyl acetate and methanol. The test of inhibition xanthine oxidase activity was using a spectrophotometer at λ = 274.79 nm, pH 7.8, substrate concentration of xanthine 0.15 mM and an incubation temperature of 30°C. Inhibition on Allopurinol as positive control has IC50 0.15 μg/mL. The result showed that methanol extract of rambutan skin had the highest inhibition percentage with IC50 3.71 μg/mL. Phytochemical screening showed that the most active extract methanol of rambutan fruit skin contain flavonoids, saponins, tannins and terpenoids.